1970
DOI: 10.1002/ijc.2910060207
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of anti‐tumor platinum compounds on DNA, RNA and protein syntheses in mammalian cells in vitro

Abstract: The inhibitory effects of anti-tumor, bacterial filament forming platinum compounds, C14 ( B ) , and Pt (11) ( NH,) , (CH,) , CI, ( C ) on DNA, RNA and protein syntheses was measured by the incorporation of 3Hthymidine, 3H-uridine, and 3H-L-leucine, respectively, into an acid-insoluble polymer in human amnion A V 3 cells. Compound A , the most effective tumor-inhibiting platinum compound, was shown to selectively inhibit D N A synthesis below 5pM and to inhibit 3H-thymidine incorporation more rapidly than 3H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
110
0
6

Year Published

1972
1972
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(120 citation statements)
references
References 10 publications
4
110
0
6
Order By: Relevance
“…Thrombocytopenia and bone marrow hypocellularity were more severe in rats receiving carboplatin, with and without WBH, than in rats given cisplatin, with and without WBH. Although severe thrombocytopenia appeared to be doselimiting for the combination of carboplatin with WBH, similar TERs of about 2 were estimated for both carboplatin The cytotoxicity of platinum compounds is generally thought to be based on reaction of the platinum molecule with nucleophilic sites on the DNA (Harder & Rosenberg, 1970). With the combination of cisplatin and hyperthermia the enhancement of cytotoxicity may be due partly to increased drug uptake in tissues , increased DNA cross-link formation (Meyn et al, 1980), alteration in drug metabolism (Zakris et al, 1987), and inhibition of DNA repair by heat (Meyn et al, 1979).…”
Section: Discussionmentioning
confidence: 88%
“…Thrombocytopenia and bone marrow hypocellularity were more severe in rats receiving carboplatin, with and without WBH, than in rats given cisplatin, with and without WBH. Although severe thrombocytopenia appeared to be doselimiting for the combination of carboplatin with WBH, similar TERs of about 2 were estimated for both carboplatin The cytotoxicity of platinum compounds is generally thought to be based on reaction of the platinum molecule with nucleophilic sites on the DNA (Harder & Rosenberg, 1970). With the combination of cisplatin and hyperthermia the enhancement of cytotoxicity may be due partly to increased drug uptake in tissues , increased DNA cross-link formation (Meyn et al, 1980), alteration in drug metabolism (Zakris et al, 1987), and inhibition of DNA repair by heat (Meyn et al, 1979).…”
Section: Discussionmentioning
confidence: 88%
“…Some of these complexes are also very potent broad-spectrum antitumour agents. Indeed, it is considered that Pt" complexes inhibit DNA synthesis by direct interaction with the nucleic acid (Harder & Rosenberg, 1970). In addition, it has been found that this interaction depends on heterocyclic base composition MiUard, Macquet & Theophanides, 1975), guanine being the preferred site of attack, at least at low complex/DNA ratios, and induces localized conformational changes in DNA (Munchausen & Rahn, 1975;Tamburro, Celotti, Furlan & Guantieri, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…In mammalian, as well as in bacterial cells, DNA is the preferential target for Pt compounds. For cis-Pt(NH3)2CI2 this interaction results in lesions that selectively block DNA replication (4,5). In this respect, cis-Pt compounds behave similar to other drugs such as alkylating and radiomimetic agents.…”
mentioning
confidence: 99%